Un parto in maschera? Osservazioni sulla terracotta antropomorfica calcolitica della Fondazione Pierides (Larnaca, Cipro) (Mantichora. Italian Journal of Performance Studies, 2020)
A well-known anthropomorphic asksos of a seated male, first described in 1981 as an enthroned ithyphallic figure, belongs to the archaeological collection of the Pierides Foundation Museum in Larnaka In this paper, after briefly describing the terracotta as an object per se, I will move to analyze two major opposite interpretative schemes firstly proposed by Desmond Morris and Vassos Karageorghis and then by Naomi Hamilton. Although the lack of clear provenance makes contextual analysis more difficult, we might rely on three different sources of evidence in order to interpret the Pierides terracotta: figurative documents, ethnographic counterparts and literary evidence. As far as the first set of documents is concerned, the archaeological record suggests that while there is no tradition of male figures in Chalcolithic Cyprus, seated figures do have a place in the iconography of the period and they are mostly connected with pregnancy and birth-giving, such as at Middle Chalcolithic Kissonerga-Mosphilia (Period 3B). At the same time, both ethnographic counterparts and the literary analysis of ancient myth confirm the relevance of male transvestitism in the performance of the couvade, as a ritual connected with the fertility and the protection of the woman lifegiver. To conclude with, it will be argued that this threefold data-set leads us to a new interpretation of the significance and peculiar function of this terracotta in the ritual performance of the Chalcolithic community in Cyprus.